Strength and Stiffness of Composite Beams In Unbraced Frames - Fahmy, Hassan Ahmed Ezzat (My University, 1978)
Composite steel-concrete beams often form part of multi-story frames. However, very little information is available on which to base the design of composite beam-to-column connections. As a result, these connections are currently designed on the basis of the connecting steel elements. Most of the information available is limited to continuous composite beams subjected to gravity loads which may be used as a part of braced multi-story frames. Limited information is available on the behaviour of composite beams is unbraced multi-story frames subjected to combined gravity and lateral loads.
The object of this thesis is to study the behaviour of composite beams with ribbed metal deck in an unbraced multi-story frame. Of particular importance in this investigation is the effective slab width which is to be used in evaluating the strength of the composite beam at the connection and the effective slab width which is to be used in evaluating the stiffness of the composite beams in the positive and negative moment regions of an unbraced frame subjected to combined gravity and lateral loads. A combined analytical and experimental investigation was conducted.
A method of analysis has been devloped using a combination of the finite difference and finite elements methods to model the composite steel-concrete beams in the various moment regions. The analytical model was used to study the parameters affecting the effective slab widths, for strength and stiffness, and consequently the behaviour of composite beams in an unbraced frame. Curves showing the variation of the effective slab width for strength and the effective slab width for stiffness with the side ratio (L/b) and the column width to slab width ration (c/b) in the case of complete interaction and a method for evaluating the effective slab width for stiffness for any degree of interaction are presented.
The analytical model was used to study the effective slab widths for composite simple beams subjected to a central point load, and the results were compared with the different code formulae. The results showed that the AIJ formula agrees very well with the analytical results of the effective slab width for strength while the CSA S16.1 formulae provides a good estimate for the effective slab width for stiffness especially for (L/b) greater than 4.
In the experimental program, 10 composite beam-to-column connections were tested under positive moment conditions to stimulate that portion of the composite beam in an unbraced frame between the point of contraflexure and the column face and subjected to positive moment. The test results showed that the strength, stiffness and ductility depend on the (L/b) and (c/b) ratios, steel beam size, slab thickness and the existence of lateral support. The test results showed also that the composite beam-to-column connections possess sufficient rotattion capacity to enable plastic design to be applied to unbraced frams with composite beams.
The test beams were analysed using the analytical model and very good agreement was obtained between the experimental and analytical results.
Keywords: Civil Engineering; Civil Engineering